Я - вор в законе: [роман] / Евгений Сухов - Сухов Евгений Евгеньевич (Я - вор в законе, 1998)
Экземпляры: ф. 3 (20140206) / Инвентарный номер: 100627 / Цена: 30.00 / Авт.знак: С 91 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6